<span>Given:
f(0) = 2</span>
So first of all, we let x = 2012, y = 0:
<span>
Then, F(2012) = 2012 + f(0)
Since f(0) = 2, then f(2012) = 2012 + 2 = 2014.
To add, </span>the process that relates an input to an output is called a
function.
<span>There are always three main parts of a
function, namely:
</span>Input
The Relationship
The Output
The classic way of writing a function is
"f(x) = ... ".
What goes into the function
is put inside parentheses () after the name of the function: So, f(x) shows us the
function is called "f", and "x" goes in.
What a function does with the input can be usually seen as:
<span>f(x) = x2</span><span> reveals to us that function "f" takes "x<span>" and squares
it.</span></span>
Answer:
tôi không hiểu bạn nói gì
Step-by-step explanat ion :
We will translate the given statement in the problem into
x + y = 90
x - y = 90 - 86 = 4 where x and y are the angles that are complementary. solving simultaneously, x = 47 degreesy = 43 degrees.
The solution to the compound inequality given as 3x−8≤23 AND −4x+26≥63 is x ≤ 31/3 AND x ≤ -89/4
<h3>How to determine the solution to the
compound inequality?</h3>
The compound inequality is given as:
3x−8≤23 AND −4x+26≥63
Rewrite properly as:
3x − 8 ≤ 23 AND −4x + 26 ≥ 63
Add to both sides of compound inequality ,the constant in the compound inequality expression
So, we have:
3x ≤ 31 AND −4x ≥ 89
Divide both sides of compound inequality, by the coefficient of the variable x in the compound inequality expression
So, we have:
x ≤ 31/3 AND x ≤ -89/4
hence, the solution to the compound inequality given as 3x−8≤23 AND −4x+26≥63 is x ≤ 31/3 AND x ≤ -89/4
Read more about compound inequality at
brainly.com/question/1604153
#SPJ1